Rapid screening and quantitative determination of bioactive compounds from fruit extracts of Myristica species and their in vitro antiproliferative activity. (15th November 2016) - Pandey, Renu; Mahar, Rohit; Hasanain, Mohammad; Shukla, Sanjeev K.; Sarkar, Jayanta; Rameshkumar, K.B.; Kumar, Brijesh
Highlights: Twenty-one compounds were identified from four Myristica species by HPLC-QTOF-MS/MS. Seventeen compounds were reported first time from M. beddomeii and sixteen from M. fatua. Quantification of five major bioactive compounds was carried out by UHPLC-QqQLIT -MS/MS. Highest total content of five major active compounds was found in mace of M. fragrans. Evaluation of in vitro anti-proliferative activity revealed potent activity in Myristica species. Abstract: Efficient and sensitive LC–MS/MS methods have been developed for the rapid screening and determination of bioactive compounds in different fruit parts of four Myristica species, viz., Myristica beddomeii, Myristica fragrans, Myristica fatua and Myristica malabarica . Twenty-one compounds were identified and characterized on the basis of their accurate mass and MS/MS fragmentation pattern using HPLC-QTOF-MS/MS and NMR analysis. Quantitative determination of five major bioactive compounds was performed using multiple-reaction monitoring mode with continuous polarity switching by UHPLC-QqQLIT -MS/MS. Moreover, in vitro antiproliferative activity of these Myristica species was evaluated against five human cancer cell lines A549, DLD-1, DU145, FaDu and MCF-7 using SRB assay. Seventeen phytoconstituents were identified and reported for the first time from M. beddomeii and sixteen from M. fatua. Quantification result showed highest total content of five major bioactive compounds in mace of M. fragrans . Evaluation of in vitro antiproliferative activity revealed potent activity in all investigated species except M. fragrans.